Effect of extraction method on the antioxidant activity of cashew apples collected in northern Côte d’Ivoire - TIEKPA , Wawa Justine; KOUANGBE, Mani Adrien; DJOUPO , Agnon Prisca; TOURE , Abdoulaye (Journal of Drug Delivery and Therapeutics, 2025)
The aim of this study was to evaluate the effect of extraction method on the antioxidant activity of cashew apples. The aqueous extracts studied were obtained either by maceration or decoction. Their polyphenol and flavonoid contents were determined by spectrophotometric assay, then their free radical scavenging activity was assessed using the DPPH method. Characterization of the phenolic compounds in the various extracts showed that the DAd, AMd and SId aqueous extracts obtained by decoction contained higher levels of polyphenols at 197.15 ±2.65, 183.49 ± 3.55 and 161.16 ± 2.02 mg EQ/g extract respectively, and higher levels of flavonoids at 274.32 ± 2.65, 196.44 ± 2.65 and 193.55 ± 2.31 mg EQ/g extract respectively. DAm, AMm and Sim, extracts obtained by maceration had the lowest phenolic compound contents of 170.09 ± 2.74, 168.19 ± 3.45 and 123.38 ± 3.65 mg EQ/g extract respectively, and flavonoid contents of 158.94 ± 3.57, 147.40 ± 1.45 and 110.86 ± 1.02 mg EQ/g extract respectively. Taking harvest sites into account, extracts from the DAO site were richer in phenolic compounds than extracts from other sites. Determination of antioxidant activity showed that decoctions have better antioxidant activity than macerations. This anti-free radical activity is thought to be correlated with phenolic compound content. The good antioxidant activity would justify its use in traditional diets and therapeutics. Keywords: Anacardium occidentalis, cashew apple, antioxidant activity, extraction method, food and therapeutic use